The impact on people's holding intention of bitcoin by their perceived risk and value. Issue 1 (1st January 2019) - Huang, Weilun
Abstract: This article has developed a structural equation model, aimed at evaluating the impact factors on people's holding intention of Bitcoin, a cryptocurrency created by the Blockchain technology. Specifically, this study directs its attention on the Bitcoin holder's perceived value and risk, the moderating effects of gender, income, age, and the experience of digital token provided by the respondents. The conclusions are: (1) The majority of individuals do not have any understanding of the values or risks of Bitcoin; (2) The more transaction and speculative risks of Bitcoin people perceive, the less government intervention they are expected to have. Nevertheless, even if government intervention is necessary, it would not impact their holding intention; (3) The higher value of Bitcoin people perceive, the more government intervention people would prefer. Despite this preference, people's holding intention remains intact. However, its degree of influence is definitely less conspicuous than the above effect of the second conclusion; and (4) The government advocacy about the values and risks of Bitcoin should be differentiated by the more nuanced factors such as gender, income, the experience of digital token usage, and age of users, in order to obtain an effective regulation of Bitcoin.